PENGARUH PERSEPSI TRANSPARANSI ALIRAN DANA PAJAK, KUALITAS PELAYANAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN PAJAK DI KPP PRATAMA SAWAHAN SURABAYA - Yumico Patricia Wiratama; Hari Hananto (Perpustakaan Universitas Surabaya, 2018)
Low tax compliance in Indonesia is still an obstacle for the government, especially tax officers. As a result, Indonesia’s tax ratio in 2017 is still at 11%. Factors affecting tax compliance then become an interesting topic for government, academics, or public in general. Moreover, with a number of tax scandals emerging in past years, government has to work hard to regain public’s good view on taxations. Therefore, the goal of this study is to find out whether perception of tax transparency, service quality, and tax penalty affect tax compliance. Data from this study is gained from questionnaires given to 100 individual tax payers who are registered and effective in Kantor Pelayanan Pajak Pratama Sawahan Surabaya and then analyzed with multiple linear regression analysis. The result from F-test and t-test shows that perception of tax penalty is the only variable with significant and negative effect to tax compliance, while perception of tax transparency and perception of service quality have no significant positive effect on tax compliance. Despite that, the three variables together have an effect on tax compliance, although they’re only able to explain 6.5% of tax compliance.